Limits to exogenous glucose oxidation by skeletal muscle during prolonged, moderate-intensity exercise in man - Hawley, John Alan (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Several factors may determine the rate. at which exogenous carbohydrate (CHO) is utilised by the human working muscles during prolonged (> 90 min moderate-intensity (63% of peak sustained power output [PPO]) exercise. These include i) the rate of gastric emptying of an ingested fluid, ii) the rate of digestion, absorption and subsequent transport of glucose into the systemic circulation, and iii) the rate of glucose uptake and oxidation by the working muscles. To test the hypothesis that the rate of gastric emptying is the primary factor limiting the rate of CHO delivery to the working muscles during exercise, uniformly labelled ¹⁴carbon (U-¹⁴C) tracer techniques were used in association with conventional gas exchange measurements and post-exercise gastric aspiration to compare the rates of gastric emptying, intestinal CHO delivery and ingested CHO oxidation from 15 g/100 ml solutions of glucose, maltose, a 22 chain-length glucose polymer, and an isocaloric 'soluble' starch preparation. Two groups of six highly-trained male cyclists or triathletes each ingested two of the test drinks which were given as a 400 ml loading bolus immediately before and then as eight 100 ml feedings at 10 min intervals during 90 min of continuous cycling at a work rate of 63% of PPO (~70% of maximal oxygen consumption [VO₂ₘₐₓ]).